KRITIK OTORITARIANISME TEKS DENGAN PISAU HERMENEUTIK; KAJIAN TERHADAP PEMIKIRAN KHALED M ABOU KHALED - Alfi Qonita Badi’ati (INJECT (Interdisciplinary Journal of Communication), 2016)
Khaled is one of scholars who is really anxious to the Islamic law. He against the fatwas produced by some institutions or certain scholars, especially, a fatwa regarding fiqh as the final solutions of ummah. Eventually, these instructions are considered to be authoritarian or discrimination for the weak class. The methodological errors in understanding the Islamic resources are the causes of the emergence of authoritarianism phenomenon. Khaled offers the hermeneutic methode to solve these problems. Methodology of Khaled’shermeneutic consists of three elements; determination of meaning, text competence, and the concept of representation in Islam. Using the hermeneutic approach, Islamic law produced, is expected to be authoritative, innovative, and dynamic.AbstrakKhaled merupakan salah satu cendikiawan muslim yang tertarik dibidang hukum Islam. Ia menentang fatwa yang dibuat beberapa lembaga atau beberapa cendikiawan khususnya fatwa mengenai fiqih sebagai solusi akhir umat. Pada akhirnya fatwa ini dianggap otoriter dan diskriminatif terhadap kalangan lemah. Kesalahan metode dalam memahami sumber-sumber kajian islam merupakan penyebab munculnya fenomena keotoriteran tersebut. Khaled menawarkan sebuah metode hermeneutik untuk mengatasi masalah tersebut. Metode hermeneutik Khaled terdiri dari tiga elemen: penentuan makna, kompetensi teks, dan konsep penafsiran dalam Islam. Dengan menggunakan pendekatan hermeneutik, hukum Islam yang terbentuk diharapkan menjadi berwibawa, inovatif, dan dinamis.